Autonomic adjusting of activity of cardio-vessel system of girls of the prepubescence period, engaged in dancing aerobic - Romanchuk А.P; Grechko O.D; Perevoschikov Yu.A (Kharkov National Pedagogical University, 2010)
The vegetative adjusting of activity of the cardio-vessel system of girls is investigational. In an experiment took part girls of 9-12 years old. A type of sport is a dancing aerobics. The indexes of general power of spectrum of variability of cardiac rhythm are presented, systole and diastole arteriotony. Motion of the adaptation re-erecting is appraised under influence of the physical loadings in the conditions of current and operative control. Certain change activity and tone of vegetative influences on the cardio-vessel system. They determine the features of the further adaptation re-erecting in an organism.